General Characteristics of Eastern Indonesian Household Dietary Diversity Score - Maretalinia, Maretalinia; Suryani, Dyah; Angriani, Yayu (AMPLITUDO : Journal of Science and Technology Innovation, 2024)
Household dietary diversity score (HDDS) is a crucial indicator of food security and nutritional outcomes. The data collection was done from 2017 to 2018 in Eastern Indonesia. This study aimed to capture the characteristics of HDDS based on district, province, religion, and head of household age. This study used secondary data from the Coastal Community Development Project (CCDP), IFAD Impact Assessment Survey 2018. The total sample of this study was 2,884 households. The HDDS was calculated based on the score of 12 food groups and presented in a bar graph using STATA version 17. The result revealed that the lowest HDDS was found in the Kupang district, East Nusa Tenggara Province, Confucianism or Konghucu Religion, and 15 to 25 years of head of household age. Household dietary diversity score is a critical measure of food security and nutritional status, reflecting a household's access to a variety of foods. Understanding and addressing these determinants are essential for improving household dietary diversity and ultimately enhancing nutrition outcomes.